Evaluasi Kesesuaian Penggunaan Lahan Berdasarkan Kemampuan Lahan dengan Metode Skoring di Kabupaten Aceh Besar - Muzailin Affan; Fadhil Hidayatullah; Dahlan Dahlan (Fakultas Teknik, 2022)
Aceh Besar District is designated as an Integrated Economic Development Zone (KAPET) with the potential for rapid economic and regional development. This has an effect on the demand for land and housing for development which at any time can increase sharply, if not accompanied by certain policies and considerations it can cause a decrease in land capacity and affect the sustainable development of the area. The demand for more rapid development can lead to uncontrolled land-use change, changes in spatial use, and trigger disasters that affect community economic development. This study aims to evaluate the suitability of land use based on the ability of the land to use spatial data in Aceh Besar District. This study uses the scoring method for spatial analysis that refers to the Permen PU No. 20 / PRT / M / 2007. The results showed that the land capability unit of Aceh Besar District had an average weight of 3, except for the land capability of the carrying capacity and foundation stability was less with a weight of 2-3. The land capability value of the Aceh Besar Regency is 71-121, with the highest land capability class being class c (value 83-109) covering an area of 215,861.16 Ha or 74.96% and is included in the medium development classification. The suitability of land use in Aceh Besar District has a high level of land-use suitability with an area corresponding to 277.887,38 Ha or 96,56% and an area according to conditionally covering 9.895,94 Ha or 3.44%, while the level of land use mismatch in Aceh Besar District is classified as low with an area of 2,15 Ha or 0,0007%.